2020
DOI: 10.3389/fped.2020.604918
|View full text |Cite
|
Sign up to set email alerts
|

Social and Behavioral Difficulties in 10-Year-Old Children With Congenital Heart Disease: Prevalence and Risk Factors

Abstract: Children with congenital heart disease (CHD) may be at increased risk for neurodevelopmental impairments. Long-term behavioral profiles and respective risk factors are less frequently described. The aim of this study was to evaluate multidimensional behavioral outcomes and associated medical, psychological, and social risk factors in children with complex CHD. At 10-years of age, 125 children with CHD were assessed for general behavioral difficulties, attention deficit hyperactivity disorder (ADHD)-related beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 54 publications
2
30
1
Order By: Relevance
“…At 10 years of age, only children without genetic or syndromal disorders were assessed. The REA-CHOUT study focuses on the neurodevelopmental outcome of these children [44,45]. Families were eligible for the current study on well-being during the COVID-19 pandemic if the child had participated in the neurodevelopmental assessment and the parents had completed a set of questionnaires on child and parent well-being between January 2013 and mid-March 2020 as part of the EpoKids or the REACHOUT study (T0: prior to the implementation of measures to reduce COVID-19 in Switzerland).…”
Section: Participants and Study Proceduresmentioning
confidence: 99%
“…At 10 years of age, only children without genetic or syndromal disorders were assessed. The REA-CHOUT study focuses on the neurodevelopmental outcome of these children [44,45]. Families were eligible for the current study on well-being during the COVID-19 pandemic if the child had participated in the neurodevelopmental assessment and the parents had completed a set of questionnaires on child and parent well-being between January 2013 and mid-March 2020 as part of the EpoKids or the REACHOUT study (T0: prior to the implementation of measures to reduce COVID-19 in Switzerland).…”
Section: Participants and Study Proceduresmentioning
confidence: 99%
“…49,50 Similarly, in children with CHD, behavioral problems related to emotions and social interactions, and attention-related symptoms have been reported. 11,51 By directly comparing children born VPT and children with CHD using appropriate statistical methods, the current study demonstrated that the pattern of behavioral problems may not be considered similar between these clinical groups.…”
Section: Discussionmentioning
confidence: 88%
“…Sociobehavioral difficulties have previously been reported in children with CHD (Bellinger et al, 2009; Clancy et al, 2019; Mussatto et al, 2018; Werninger et al, 2020). There is also emerging evidence showing that CHD survivors have an increased risk of autism spectrum disorder (ASD) symptoms (Bean Jaworski et al, 2017) or of meeting ASD diagnostic criteria (Razzaghi et al, 2015; Sigmon et al, 2019; Tsao et al, 2017).…”
mentioning
confidence: 85%
“…to disruption in youth with chronic illness (Martinez et al, 2011), epilepsy (Caplan, 2019;Stewart et al, 2019), acquired brain injury (Anderson et al, 2017;Ganesalingam et al, 2011;Ryan et al, 2014Ryan et al, , 2019, preterm birth (Alduncin et al, 2014;Marleau et al, 2020), or neurodevelopmental disorders (Berard et al, 2017;Brinton & Fujiki, 2005;Nixon, 2001;Staikova et al, 2013;Stichter et al, 2010). Sociobehavioral difficulties have previously been reported in children with CHD (Bellinger et al, 2009;Clancy et al, 2019;Mussatto et al, 2018;Werninger et al, 2020). There is also emerging evidence showing that CHD survivors have an increased risk of autism spectrum disorder (ASD) symptoms (Bean Jaworski et al, 2017) or of meeting ASD diagnostic criteria (Razzaghi et al, 2015;Sigmon et al, 2019;Tsao et al, 2017).…”
mentioning
confidence: 99%